HUMANE EDUCATION AND CHILD CHARACTER DEVELOPMENT: A CONCEPTUAL REVIEW OF CORRELATION BETWEEN ANIMAL WELFARE EDUCATION AND PROSOCIAL BEHAVIOR - Kristiana, Naomi (Buletin Veteriner Udayana; Vol. 15 No. 5 Oktober 2023DO - 10.24843/bulvet.2023.v15.i05.p28, 2023)
Humane education is an educational program that does not only focus on supporting the animal’s well-being but also generally gives positive impacts on children’s character development. Characters were born from the process of learning and habit practices that were carried out at early age. Therefore, character education should be taught early. Positive character development in children, for example, empathy and compassion, will contribute to the emergence of prosocial behavior. This could become preventive action or solution to anticipate the increasing violence trend that is directed either to humans, animals or, the environment.